Simulation of PWM inverters using MATLAB - Ismail Nasarudin, Shahrizuan (2004)
This project presents simulations of Pulse Width Modulation (PWM) inverters using MATLAB. Since MATLAB has the necessary numerical tools to solve non-linear differential equations, simulation can be carried out by developing system differential equations of the PWM inverters. More importantly, due to the computer aided design (CAD) tools available in the MATLAB environment; a CAD package for regulated inverters can easily be developed. It is shown that the accuracy of the simulation results using MATLAB is higher compared to that using PSPICE. However, the simulation speed of MATLAB is much faster.